The Effectiveness of Project-Based Learning Assisted by the Digital IoT Blynk Simulation on Improving the Practical Skills of Grade X Mechatronics Students at SMKN 8 Malang - Adelia, Cheri; Ningrum, Gres Dyah Kusuma (Journal of Educational Sciences, 2025)
The rapid development of digital technology in the Society 5.0 era has driven the need for vocational education to adapt to industrial automation demands. However, practical learning in many vocational schools remains conventional, limiting students’ exposure to IoT-based systems. This study aimed to determine the effectiveness of the Project-Based Learning (PjBL) model integrated with the IoT Blynk platform in improving students’ practical skills. The research employed a quantitative approach with a quasi-experimental design using two groups: an experimental class applying IoT Blynk–based PjBL and a control class using conventional methods. Data were collected through pretests, posttests, and observations, and analyzed using the Wilcoxon and Mann-Whitney tests, as well as the N-Gain score. The results showed significant differences between groups (U = 204.500; Z = -4.796; p < 0.001). The N-Gain score for the experimental class (0.62) was higher than for the control class (0.39), indicating medium–high improvement. These findings confirm that integrating Blynk IoT with PjBL effectively enhances students’ practical skills, motivation, and readiness for Industry 4.0.